2(3x+6)=-49+19

Simple and best practice solution for 2(3x+6)=-49+19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x+6)=-49+19 equation:


Simplifying
2(3x + 6) = -49 + 19

Reorder the terms:
2(6 + 3x) = -49 + 19
(6 * 2 + 3x * 2) = -49 + 19
(12 + 6x) = -49 + 19

Combine like terms: -49 + 19 = -30
12 + 6x = -30

Solving
12 + 6x = -30

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + 6x = -30 + -12

Combine like terms: 12 + -12 = 0
0 + 6x = -30 + -12
6x = -30 + -12

Combine like terms: -30 + -12 = -42
6x = -42

Divide each side by '6'.
x = -7

Simplifying
x = -7

See similar equations:

| z+9/=2.1 | | 10-4s+2s= | | N+(-16)=0 | | 24a-24= | | 5z+3=5z-z | | -3a+7+4a=16-25 | | 14+7y-5= | | 5r-5s=0 | | 10x+72=23x+6 | | 3(m-2)+5=8-2(m-4) | | 3+3r=9 | | 4x+6=-1x+1 | | 17+3(c-2)-11c=-7(c+2)+14 | | 3x+5x=19+5 | | 9-K=k+3 | | 2x+z=7 | | (u+5)/8=2 | | X+14+19(3)=17 | | 1.8+9=5.7-6 | | 4n=84 | | 40-f=27 | | 4x-12=-2+21 | | 2(3n)=12 | | 2d+3=-16 | | -42=4r-18 | | 3x+2x-62=18 | | x+5+60+60x=180 | | 5s-16=37s | | 3+6+m+12+5=30 | | (5y+9)(6+y)=0 | | 3x+y+z=12 | | sin^2(x)-sin(x)cos(x)=0 |

Equations solver categories